Community development workers programme: mentoring for social transformation in the public service in post-apartheid South Africa - Geber, Hilary; Mothlake, Bona (Inderscience, 2008)
The new public sector community development workers (CDWs) programme was established in 2004 following ineffective service delivery through chronic under-spending on annual budgets in post-apartheid South Africa. CDWs receive training in learnerships within the National Skills Development Strategy to ensure access to and spending of local government poverty alleviation funding allocated for housing, childcare grants, and pensions and other services. As learnership mentors are mandatory, this research investigates the formal mentoring of CDWs after learnership programmes. CDWs and their mentors from two large municipalities participated. The main findings show inadequate formal mentoring of CDWs despite legislative requirements. Crucial mentoring for career development and psychosocial support is patchy and uneven. Social transformation of communities and access to government services and grants is likely to take longer than anticipated if CDWs are not adequately mentored during their training and in workplace learning.
Keywords: Public sector CDWs; community development workers; human capital development; organisational learning; learnerships; mentoring; organisational change; public service; post-apartheid South Africa; social transformation; local government; poverty alleviation funding.